Layoff taxes, unemployment insurance, and business cycle fluctuations - Steffen Ahrens; Nooshin Nejati; Philipp L. Pfeiffer (Kiel Institute for the World Economy (IfW), 2015)
This paper studies the role of labor market institutions in business cycle fluctuations. We develop a DSGE model with search and matching frictions and incorporate a US unemployment insurance experience rating system. Layoff taxes based on experience rating finance the cost of unemployment benefits and create considerable employment adjustment costs. Our framework helps realign the search and matching model with the empirical properties of its most salient variables. The model reproduces the negative correlation between vacancies and unemployment, i.e., the Beveridge curve. Simulations show that the model generates more cyclical volatility in its key variable - the ratio of job vacancies to unemployment (labor market tightness). Moreover, layoff taxes reduce the excess sensitivity of job destruction found in Krause and Lubik (2007) and strengthen the negative correlation of job creation and job destruction. Thus, the model matches key labor market data while incorporating an important feature of the US labor market.
Keywords: E24; J64; J65; 330; search and matching; experience rating; unemployment insurance; Beveridge curve